Full‐Order observer design for nonlinear complex large‐scale systems with unknown time‐varying delayed interactions. Issue 2 (11th August 2014) - Phat, Vu N.; Thanh, Nguyen T.; Trinh, Hieu
Abstract : This article is concerned with the problem of state observer for complex large‐scale systems with unknown time‐varying delayed interactions. The class of large‐scale interconnected systems under consideration is subjected to interval time‐varying delays and nonlinear perturbations. By introducing a set of argumented Lyapunov–Krasovskii functionals and using a new bounding estimation technique, novel delay‐dependent conditions for existence of state observers with guaranteed exponential stability are derived in terms of linear matrix inequalities (LMIs). In our design approach, the set of full‐order Luenberger‐type state observers are systematically derived via the use of an efficient LMI‐based algorithm. Numerical examples are given to illustrate the effectiveness of the result. © 2014 Wiley Periodicals, Inc. Complexity 21: 123–133, 2015